MUTU PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS DI INDONESIA - Firdausyi, Muhammad Fajar (Educatus, 2024)
Inclusive education in Indonesia still faces various challenges in providing quality education services for children with special needs. However, the quality of inclusive education for them remains an inadequately resolved issue. This research is important for comprehensively examining the quality of inclusive education in Indonesia, identifying influencing factors, and formulating solutions to enhance its quality. The study aims to identify and analyze factors influencing the quality of inclusive education for children with special needs in Indonesia. It employs a qualitative descriptive method with a case study approach. Data is collected through observations, interviews, and documentation. The research findings indicate that the quality of inclusive education in Indonesia is still suboptimal. Factors influencing it include uneven access, inadequate infrastructure, undertrained teachers, and minimal support.